Experimental study on micro-damage identification in reinforced concrete beam with wavelet packet and DIC method. (20th June 2019) - Zhao, Binna; Lei, Dong; Fu, Jianjun; Yang, Liqun; Xu, Wenxiang
Highlights: The micro-damage identification of the concrete beam is proposed. The method is based on the wavelet packet and DIC technique. The method has greater advantages for micro-damage identification than the vibration test. The method can provide an early warning of micro-damage, and determine its location and degree. Abstract: Structural damage identification has become a research hotspot in the field of science and engineering. Previous predominant lines of research on structural damage identification methods focused on macroscopic damage, which is visible to naked eyes, but there are few studies on structural micro-damage identification. Towards this end, this paper proposes a combination of digital image correlation (DIC) technique and wavelet packet analysis for micro-damage identification and to achieve real-time early warning of micro-damage initiation in concrete structures. This work implements a four-point bending test of reinforced concrete beams, as well as adopts the step loading and unloading method, following which, the beam acceleration response signal and the damage strain field are collected. Subsequently, the collected response and excitation are processed to obtain the excitation response function, reflecting the dynamic structural state. The wavelet packet is used to process the excitation response function and image under each load level to obtain the corresponding energy spectrum. In this way, the respective micro-damage identification indices are calculated for comparison. The experimental results show that the proposed methodology can properly characterize the damage state of structures under various stages of stress, provide a warning for the initiation of micro-damage, and even accurately determine the location and degree of micro-damage, based on the damage strain field.